2012
DOI: 10.1093/protein/gzs083
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of dual-functional hybrid glucanases

Abstract: 1,3-1,4-β-D-Glucanase (lichenase) and 1,3-β-D-glucanase (laminarinase) are fibrolytic enzymes which play an important role in the hydrolysis of polysaccharide components. Both of these glucanases have been employed in a number of industrial applications. This study aims to improve or combine the novel properties of both glucanases in an attempt to create desirable hybrid enzymes with economic benefits for industrial applications. A truncated and mutated 1,3-1,4-β-D-glucanase gene (TFs(W203F)) from Fibrobacter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Liu et al . confirmed an increase in substrate specificity in a chimeric enzyme of lichenase and laminarinase . Furtado et al .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Liu et al . confirmed an increase in substrate specificity in a chimeric enzyme of lichenase and laminarinase . Furtado et al .…”
Section: Discussionmentioning
confidence: 78%
“…Liu et al reported that a chimeric enzyme of xylanase and glucanase showed increased xylanase activity when compared with the original xylanase when joined in the order of xylanaseglucanase, but showed reduced xylanase activity when glucanase was located in the N-terminus (37). Liu et al confirmed an increase in substrate specificity in a chimeric enzyme of lichenase and laminarinase (38). Furtado et al reported that a chimeric enzyme of laccase and b1,3-1,4-glucanase showed 30% higher Vmax and 20% higher hydrolysis (39).…”
Section: Discussionmentioning
confidence: 90%
“…Considering the highest optimum pH values, 9.0-10.0 in Bacillus sp., 8.5 in Zobellia galactanivorans and 6.0-7.0 in Thermotoga maritima can be given as examples (Nogi and Horikoshi, 1990;Liu et al, 2012;Labourel et al, 2014). Optimum pH of β-(1,3)-glucanase forms isolated from Cellulosimicrobium cellulans varies according to the substrate, but is around 5.5-8.0.…”
Section: Chemical Structure Of Glucanmentioning
confidence: 99%
“…The following approaches are typically used in protein engineering: deletions (excision of domains and/or individual amino acids); random and directed mutagenesis; grouping of two or more enzyme catalytic modules; and circular permutation (CP) method [4][5][6][7][8][9]. Note that the CP method is a powerful molecular tool for altering protein sequences and, as a consequence, their structure [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…An end-to-end fusion is frequently used when engineering bifunctional proteins to connect two enzymes [8,[13][14][15][16] using different approaches, for example, by optimization of peptide linkers [14] or through all-atom molecular dynamics simulations [16]. However, the chimeric enzymes constructed with the help of this method are frequently more susceptible to proteolytic degradation and structural instability [17].…”
Section: Introductionmentioning
confidence: 99%